Two/Three-dimensional Battery Pack Topologies and Their Internal Short Circuit Detectability - Paek, Sung Wook; Kim, Sangtae; Rayappan, Christober Vinoth Raj (2019 3RD IEEE CONFERENCE ON CONTROL TECHNOLOGY AND APPLICATIONS (IEEE CCTA 2019), 2019)
Electrification of transportation and energy storage systems is accelerating the advent of battery "systems of systems." Due to high complexity thereof, a number of challenges exist in battery management such as charge balancing and anomaly detection. Internal short circuit (ISC) is one of the most common and hazardous anomalies, and a few methods have been proposed to detect it inside a serial-parallel (two-dimensional) battery network. This paper extends the previous work and proposes a novel concept of three-dimensional battery packs. It follows the industry practices of constructing a pack from modules consisting of batteries, but use of an extra dimension and additional current paths enhance ISC detectability with the minimal use of current sensors. This paper reports ISC simulation results from the proposed 3D battery pack topologies.